Effect of gillnet mesh size on catch efficiency and bycatch in the Greenlandic lumpfish (Cyclopterus lumpus) fishery - Malthe Kjølhede Ahlmann Olesen; Bent Herrmann; Rikke Petri Frandsen; Flemming R. Merkel; Cas Van Der Kaaden; Søren Post (Estuarine, Coastal and Shelf Science, 2025)

Drivers of Interspecific Spatial Segregation in Two Closely‐Related Seabird Species at a Pan‐Atlantic Scale - Anne‐Sophie Bonnet‐Lebrun; Jason Matthiopoulos; Rémi Lemaire‐Patin; Tanguy Deville; Robert Barrett; Maria I. Bogdanova; Mark Bolton; Signe Christensen‐Dalsgaard; Francis Daunt; Nina Dehnhard; Sébastien Descamps; Kyle Elliott; et al. (Journal of Biogeography, 2025)
Aim Ecologically similar species living in sympatry are expected to segregate to reduce the effects of competition where resources are limiting. Segregation from heterospecifics commonly occurs in space, but it is often unknown whether such segregation has underlying environmental causes. Indeed, species could segregate because of different fundamental environmental requirements (i.e., ‘niche divergence’), because competitive exclusion at sympatric sites can force species to either change the habitat use they would have at allopatric sites (i.e., ‘niche displacement’) or to avoid certain areas, independently of habitat (i.e., ‘spatial avoidance’). Testing these hypotheses requires the comparison between sympatric and allopatric sites. Understanding the competitive mechanisms that underlie patterns of spatial segregation could improve predictions of species responses to environmental change, as competition might exacerbate the effects of environmental change. Location North Atlantic and Arctic. Taxa Common guillemots Uria aalge and Brünnich's guillemots Uria lomvia. Methods Here, we examine support for these explanations for spatial segregation in two closely‐related seabird species, common guillemots ( Uria aalge ) and Brünnich's guillemots ( U. lomvia ). For this, we collated a pan‐Atlantic data set of breeding season foraging tracks from 1046 individuals, collected from 20 colonies (8 sympatric and 12 allopatric). These were analysed with habitat models in a spatially transferable framework to compare habitat preferences between species at sympatric and allopatric sites. Results We found no effect of the distribution of heterospecifics on local habitat preferences of the focal species. We found differences in habitat preferences between species, but these were not sufficient to explain the observed levels of spatial segregation at sympatric sites. Main Conclusions Assuming we did not omit any relevant environmental variables, these results suggest a mix of niche divergence and spatial avoidance produces the observed patterns of spatial segregation.

An ecologically sound and participatory monitoring network for pan‐Arctic seabirds - Manon Clairbaux; Mia Rönkä; Tycho Anker‐Nilssen; Yuri Artukhin; Jóhannis Danielsen; Maria Gavrilo; Grant Gilchrist; Erpur Snær Hansen; April Hedd; Robert Kaler; Kathy Kuletz; Bergur Olsen; et al. (Conservation Biology, 2024)
In a warming Arctic, circumpolar long‐term monitoring programs are key to advancing ecological knowledge and informing environmental policies. Calls for better involvement of Arctic peoples in all stages of the monitoring process are widespread, although such transformation of Arctic science is still in its infancy. Seabirds stand out as ecological sentinels of environmental changes, and priority has been given to implement the Circumpolar Seabird Monitoring Plan (CSMP). We assessed the representativeness of a pan‐Arctic seabird monitoring network focused on the black‐legged kittiwake ( Rissa tridactyla ) by comparing the distribution of environmental variables for all known versus monitored colonies. We found that with respect to its spatiotemporal coverage, this monitoring network does not fully embrace current and future environmental gradients. To improve the current scheme, we designed a method to identify colonies whose inclusion in the monitoring network will improve its ecological representativeness, limit logistical constraints, and improve involvement of Arctic peoples. We thereby highlight that inclusion of study sites in the Bering Sea, Siberia, western Russia, northern Norway, and southeastern Greenland could improve the current monitoring network and that their proximity to local populations might allow increased involvement of local communities. Our framework can be applied to improve existing monitoring networks in other ecoregions and sociological contexts.

Correction: Feasibility and knowledge gaps to modeling circumpolar seabird bycatch in the Arctic - Ingrid L. Pollet; Yuri Artukhin; Signe Christensen-Dalsgaard; Erpur Hansen; Kathy J. Kuletz; Flemming Ravn Merkel; Guðjón Már Sigurðsson; Hallvard Strøm; Jennifer F. Provencher; Mark L. Mallory (Polar Biology, 2024)

Thick-billed Murres in breeding pairs migrate and overwinter far apart but in similar photic environments - Nicholas P. Huffeldt; Manuel Ballesteros; Barbara Helm; Jannie F. Linnebjerg; Flemming R. Merkel; Anders Mosbech; Morten Frederiksen (Journal of Ornithology, 2024)
Scheduling between mates in species with long-term pair bonds can be essential for positive fitness. The annual cycle in photoperiod is the primary environmental cue used by many animals to synchronize behavior and physiology among members of a population, and animals that migrate must have similar annual schedules to ensure successful breeding. However, we know little about whether members of mated pairs in migratory species experience similar photic environments across the year, which could allow for synchronization in annual phenology. Here, we used light-based geolocation to estimate positions of mated pairs of Thick-billed Murres ( Uria lomvia , a seabird a.k.a. Brünnich’s Guillemot) which bred above the northern polar circle in Greenland. We tested the hypothesis that individuals in mated pairs occur in more similar locations and photic environments than randomly matched females and males. We found no difference in the amount of spatial separation or in the photic environment between mates and randomized heterosexual pairings. In general, the distance between females and males ranged from 1,198.5 km during August to 737.4 km during January. The sexes remained in photic environments with highly correlated photoperiods and moderately correlated times of solar noon in UTC. The spatial separation of, but similar photic environments experienced by, female and male murres regardless of pair status is probably adaptive by facilitating the synchronization of annual schedules between sexes, while allowing individuals in mated pairs the freedom to pursue the best foraging opportunities during migration and overwintering independent of their mate.

Feasibility and knowledge gaps to modeling circumpolar seabird bycatch in the Arctic - Ingrid L. Pollet; Yuri Artukhin; Signe Christensen-Dalsgaard; Erpur Hansen; Kathy J. Kuletz; Flemming Ravn Merkel; Guðjón Már Sigurðsson; Hallvard Strøm; Jennifer F. Provencher; Mark L. Mallory (Polar Biology, 2024)

Spatial distribution of selenium-mercury in Arctic seabirds - Marta Cruz-Flores; Jérémy Lemaire; Maud Brault-Favrou; Signe Christensen-Dalsgaard; Carine Churlaud; Sébastien Descamps; Kyle Elliott; Kjell Einar Erikstad; Alexey Ezhov; Maria Gavrilo; David Grémillet; Gaël Guillou; et al. (Environmental Pollution, 2024)

Quantifying marine traffic intensity in Northwest Greenland and the potential disturbance of two seabird colonies - Flemming Ravn Merkel; Aili Lage Labansen; Thyge Feldskou Autzen; Malene Simon; Line Hermannsen (Marine Pollution Bulletin, 2023)

Habitat when foraging does not explain temporal segregation by sex in a breeding seabird - Nicholas P. Huffeldt; Jannie F. Linnebjerg; Jérôme Fort; Flemming R. Merkel; Morten Frederiksen (Marine Biology, 2021)

Meeting Paris agreement objectives will temper seabird winter distribution shifts in the North Atlantic Ocean - Manon Clairbaux; William W. L. Cheung; Paul Mathewson; Warren Porter; Nicolas Courbin; Jérôme Fort; Hallvard Strøm; Børge Moe; Per Fauchald; Sebastien Descamps; Hálfdán Helgason; Vegard S. Bråthen; et al. (Global Change Biology, 2021)
We explored the implications of reaching the Paris Agreement Objective of limiting global warming to Alle alle , Fratercula arctica , Uria aalge , Uria lomvia and Rissa tridactyla ) using tracking data for ~1500 individuals through resource selection functions based on mechanistic modeling of seabird energy requirements, and a dynamic bioclimate envelope model of seabird prey. Future winter distributions were predicted to shift with climate change, especially when global warming exceed 2°C under a “no mitigation” scenario, modifying seabird wintering hotspots in the North Atlantic Ocean. Our findings suggest that meeting Paris agreement objectives will limit changes in seabird selected habitat location and size in the North Atlantic Ocean during the 21st century. We thereby provide key information for the design of adaptive marine‐protected areas in a changing ocean.

Circumpolar dynamics of a marine top‐predator track ocean warming rates - Sébastien Descamps; Tycho Anker‐Nilssen; Robert T. Barrett; David B. Irons; Flemming Merkel; Gregory J. Robertson; Nigel G. Yoccoz; Mark L. Mallory; William A. Montevecchi; David Boertmann; Yuri Artukhin; Signe Christensen‐Dalsgaard; et al. (Global Change Biology, 2017)
Global warming is a nonlinear process, and temperature may increase in a stepwise manner. Periods of abrupt warming can trigger persistent changes in the state of ecosystems, also called regime shifts. The responses of organisms to abrupt warming and associated regime shifts can be unlike responses to periods of slow or moderate change. Understanding of nonlinearity in the biological responses to climate warming is needed to assess the consequences of ongoing climate change. Here, we demonstrate that the population dynamics of a long‐lived, wide‐ranging marine predator are associated with changes in the rate of ocean warming. Data from 556 colonies of black‐legged kittiwakes Rissa tridactyla distributed throughout its breeding range revealed that an abrupt warming of sea‐surface temperature in the 1990s coincided with steep kittiwake population decline. Periods of moderate warming in sea temperatures did not seem to affect kittiwake dynamics. The rapid warming observed in the 1990s may have driven large‐scale, circumpolar marine ecosystem shifts that strongly affected kittiwakes through bottom‐up effects. Our study sheds light on the nonlinear response of a circumpolar seabird to large‐scale changes in oceanographic conditions and indicates that marine top predators may be more sensitive to the rate of ocean warming rather than to warming itself.

Declining trends in the majority of Greenland’s thick-billed murre (Uria lomvia) colonies 1981–2011 - Flemming Merkel; Aili Lage Labansen; David Boertmann; Anders Mosbech; Carsten Egevang; Knud Falk; Jannie Fries Linnebjerg; Morten Frederiksen; Kaj Kampp (Polar Biology, 2014)

Inferring seabird activity budgets from leg-mounted time–depth recorders - Jannie Fries Linnebjerg; Nicholas Per Huffeldt; Knud Falk; Flemming R. Merkel; Anders Mosbech; Morten Frederiksen (Journal of Ornithology, 2014)

Abundance and energy requirements of eiders (Somateria spp.) suggest high predation pressure on macrobenthic fauna in a key wintering habitat in SW Greenland - Martin Emil Blicher; Lars Maltha Rasmussen; Mikael Kristian Sejr; Flemming Ravn Merkel; Søren Rysgaard (Polar Biology, 2011)

Bowhead whales in East Greenland, summers 2006–2008 - David Boertmann; Flemming Merkel; Jan Durinck (Polar Biology, 2009)

Status of the endangered ivory gull, Pagophila eburnea, in Greenland - Olivier Gilg; David Boertmann; Flemming Merkel; Adrian Aebischer; Brigitte Sabard (Polar Biology, 2009)

Estimating prey capture rates of a planktivorous seabird, the little auk (Alle alle), using diet, diving behaviour, and energy consumption - Ann Marie Aglionby Harding; Carsten Egevang; Wojciech Walkusz; Flemming Merkel; Stéphane Blanc; David Grémillet (Polar Biology, 2009)

The diet of king eiders wintering in Nuuk, Southwest Greenland, with reference to sympatric wintering common eiders - Flemming R. Merkel; Anders Mosbech; Sarah E. Jamieson; Knud Falk (Polar Biology, 2007)

The diet of common eiders wintering in Nuuk, Southwest Greenland - Flemming R. Merkel; Sarah E. Jamieson; Knud Falk; Anders Mosbech (Polar Biology, 2006)

Endogenous reserve dynamics of northern common eiders wintering in Greenland - Sarah E. Jamieson; H. Grant Gilchrist; Flemming R. Merkel; Antony W. Diamond; Knud Falk (Polar Biology, 2006)